2016
DOI: 10.3382/ps/pew227
|View full text |Cite
|
Sign up to set email alerts
|

Blood biochemistry, thyroid hormones, and performance in broilers with ascites caused by caffeine

Abstract: Previously, we demonstrated that caffeine, a natural alkaloid, stimulates increased incidences of pulmonary hypertension syndrome (ascites) in broilers. The present study was designed to evaluate the ergogenic effects of caffeine on broiler performance and blood parameters. One-hundred-and-ninety-two Ross 308 male broiler chicks were randomly assigned at one d of age to 16 pens with 4 treatment groups. On d 3, the drinking water was supplemented with caffeine at levels of zero, 12.5, 25, and 50 mg/kg BW/day. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…The rats fed with GCN digest thus obtained extra oxidative stress, implying that the performed caseinate lactose-glycation of the Maillard-type endowed GCN digest with an unfavorable ability in the body. Furthermore, serum glucose content is governed by many factors including carbohydrate intake, carbohydrate digestibility, glycogenolysis, and insulin sensitivity [ 47 , 51 ]. The rats fed with GCN digest had inhibited α-amylase activity but higher serum glucose, and an investigation is also needed to further reveal this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…The rats fed with GCN digest thus obtained extra oxidative stress, implying that the performed caseinate lactose-glycation of the Maillard-type endowed GCN digest with an unfavorable ability in the body. Furthermore, serum glucose content is governed by many factors including carbohydrate intake, carbohydrate digestibility, glycogenolysis, and insulin sensitivity [ 47 , 51 ]. The rats fed with GCN digest had inhibited α-amylase activity but higher serum glucose, and an investigation is also needed to further reveal this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, supplementation with caffeine reduces the T3 level on days 28 and 42, and the T3/T4 ratio on day 42 only. 63 Caffeine could induce its action either by increasing the metabolic rate of premature infants, 41 elevating the release and function of TSH 24,64 or reducing the height of thyroid follicles. 24 In rats, Son et al 65 reported that caffeine could cooperate with iodine deficiency partially via the hypothalamic-pituitary-thyroid axis (HPTA) to increase the TSH level, thyroid weights, and number of thyroidal lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the direct effects of gamma-linolenic acid on the immune system and use in the treatment of many diseases, there has been a great interest in producing high concentrations of gamma-linoleic acid (Andrade, 2018). Numerous studies have been done on the enrichment of quail feed with the use of Spirulina platensis (Boiago et al, 2019), lycopene (Sahin et al, 2008), fish oil (Kamely et al, 2016), vegetation such as Liquor ice (Doğan et al, 2018), and rice bran (Gopinger et al, 2016), to enrich its eggs (Wang et al, 2007). One of the side effects of using antibiotics is the formation of antibiotic resistance.…”
Section: Introductionmentioning
confidence: 99%